Auto Flow Wells/Artsain Aquifer and its Exploration in Papumpare District (Part), Arunachal Pradesh - Bhamrah, P.J.S. (Journal of Soil and Water Conservation, 2022)
The paper embodies the results of ground water exploration studies of piestic/artesian aquifer occuring subsurface in Doinurich-Nirjuli area of Sagalee and Itanagar Capital Complex Sub- divisions of Papumpare district of Arunachal Pradesh State. The aquifer is located in Doiniukh and Naharlogun circles spread in an area of about 20 km. A flowing well has its origin in a confined aquifer, which is separated from the atmosphere by a relatively impermeable confining formation/rock horizon, which functions as an aquifuge, aquiclude or aquitard. The water in confined layer exert an upward hydrostatic pressure greater than the atmosphere on the overlying impermeable strata. This impermeable layer when punctured by drilling cause the water level to rise above top of the aquifer even above the ground surface resulting in autoflozv wells. The imaginery surface to which pressure level of ground water in the aquifer rise to be in balance with the atmospheric pressure is termed as "peizontetric head/piestic level". The artesian aquifer tapped in wells in depth range of 30 to 53 m above ground surface in Doimukh-Nirjuli area had piestic levels 0.01 to 0.35 m above ground level. The free flow discharges were estimated to be about 20 to 100 1ph (0.02 to 0.1 mihr) at the ground level, on the basis of pressure head and diameter of pipe, in the initial phase of construction of these wells. The area has three geological formations namely Siwaliks, Piedmont/older Alluvium Zone and Newer/younger Alluvium belonging to Upper Tertiary (Plio-Pleistocene) and Holocene (Recent) Epochs. Their lithology, grain size analyses and water chemical characters were studied to recommend the well assembly and utility of ground water to various purposes respectively.